Cancer-related bone pain - Davies, Andrew, 1963- (Oxford pain management library., 2007)
Cancer-related bone pain is experienced by patients with primary bone tumours such as myeloma and osteosarcoma, but is more commonly seen in patients with malignant tumours that have metastasised to bone. Bone pain is one of the most common and severe forms of pain associated with breast, prostate and lung cancer, yet little is known about the underlying mechanisms responsible for the pain. Cancer patients identify bone pain as the most disruptive cancer-related event in terms oftheir quality of life and daily functioning, and it is also associated with increased incidence of morbidity, depres.